Pengaruh Etika Kerja, Pengalaman Kerja Dan Budaya Kerja Terhadap Prestasi Kerja Karyawan (Pada Karyawan PT. Garam (Persero)) - Nailatul Hasanah; Hadi Sunaryo; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to describe work ethics, work experience, work culture and work performance of employees of PT. Garam (Persero), to determine the effect of work ethics, work experience, work culture on employee performance. This research was conducted at PT. Garam (Persero) with a sample size of 69 respondents. The data analysis technique used multiple linear regression analysis. The results of descriptive analysis show that the employees of PT. Garam (Persero) agreed on all research variables, namely work ethics, work experience, work culture and work performance. Work ethics have a significant effect on the work performance of employees of PT. Garam (Persero). Work experience has no significant effect on the work performance of employees of PT. Garam (Persero). Work culture has a significant effect on the work performance of employees of PT. Garam (Persero). Work ethics, work experience, and work culture simultaneously have a significant effect on the work performance of employees of PT. Garam (Persero).Keywords: work ethic, work experience, work culture and employee work performance.